Modifikasi Mesin Penyiang dan Penggulud Tipe Bajak Dua Sayap dan Uji Kinerjanya Pada Tiga Jenis Tanah - Gatot S. A. Fatah (Jurnal Keteknikan Pertanian, 2008)
The machine performance test of power weeder in the heavy soil shows that: Low cannot penetration, High rolling resistance and Gear box was very hot. The objectives research were: 1). Modification the power weeder for applied to the diversity texture of soil, 2). to know performance tne rubber wheel compare to iron wheel and 3). to know performance test the coulter. The methods used are: 1) to measure the land condition, such as: moisture content of soil, penetratIon resistance, shear stress, average mass diameter and roughness surface. 2) to test machine performance, such as: weeded percentage, rolling wheel, forward velocity, gasoline consumed and weeded capacity in the tree researches located. The result of the research were: 1) Design of the iron wheel can be applied to three kind of soil (light, moderate and heavy soil). In the heavy soil (Kendalpayak) weed percentage 58.33%, fuel consumption 1.231 hour1 and weed capacity was 13.17 hours ha-1; 2) Design of the rubber wheel can applied in the light soil (Muneng); 3). Coulter can be applied in ligh and moderate soil for the moisture content of soil was 21.70%. Keywords: Modification power weeder, iron wheel, gear box, coulter. Diterima: 5 Maret 2008; Disetujui: 28 Juli 2008